2017
DOI: 10.1126/scisignal.aam7464
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β receptor I/II trafficking and signaling at primary cilia are inhibited by ceramide to attenuate cell migration and tumor metastasis

Abstract: Signaling by the transforming growth factor–β (TGF-β) receptors I and II (TβRI/II) and the primary cilia-localized sonic hedgehog (Shh) pathway promote cell migration and, consequently, tumor metastasis. In contrast, the sphingolipid ceramide inhibits cell proliferation and tumor metastasis. We investigated whether ceramide metabolism inhibited TβRI/II trafficking to primary cilia to attenuate cross-talk between TβRI/II and the Shh pathway. We found that ceramide synthase 4 (CerS4)–generated ceramide stabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 71 publications
1
74
0
Order By: Relevance
“…Primary cilium has been reported to mediate TGF‐β1–induced recruitment of human bone MSCs in a SMAD3‐dependent manner . A recent study revealed that mutation of the cilia‐targeting signal abolished the trafficking of TGF‐βRI to the primary cilia . In fibroblasts from the Tg737 orpk mutant mouse, where IFT88 is mutated, clathrin‐dependent endocytosis is disrupted at stunted primary cilia, and accumulation of TGF‐β receptors and activation of SMAD2/3 are reduced .…”
Section: Discussionmentioning
confidence: 99%
“…Primary cilium has been reported to mediate TGF‐β1–induced recruitment of human bone MSCs in a SMAD3‐dependent manner . A recent study revealed that mutation of the cilia‐targeting signal abolished the trafficking of TGF‐βRI to the primary cilia . In fibroblasts from the Tg737 orpk mutant mouse, where IFT88 is mutated, clathrin‐dependent endocytosis is disrupted at stunted primary cilia, and accumulation of TGF‐β receptors and activation of SMAD2/3 are reduced .…”
Section: Discussionmentioning
confidence: 99%
“…SA-ß-galactosidase activity was also measured for paw tissues of mice from indicated genotypes using the same kit. All animal experiment protocols were approved by the Institutional Animal Care and Use Committee at the Medical University of South Carolina (27,(54)(55)(56).…”
Section: Measurement Of Senescence Aging and Tumor Suppression In Micementioning
confidence: 99%
“…Tumor volume was measured every alternative day using digital calipers and treatments were performed using oral gavage method every day. At the end of the experiment the mice were euthanized and tumor tissues were collected (27,(54)(55)(56)(57).…”
Section: Xenograft-derived Tumors In Scid Mice Expressing Stable Shtcf21mentioning
confidence: 99%
See 2 more Smart Citations